Determinan Kemampuan Keuangan Daerah Serta Strategi Peningkatannya di Provinsi Jambi - Basri, Hasan; Devita, Andri; Fahmi, Ali; Siregar, Juanda Uly (Universitas Batanghari Jambi, 2025)
The aim of this research is to determine the determinants of regional financial capacity and strategies for improving it in Jambi Province. This research is included in the quantitative descriptive research category. The analytical tools used in the research are multiple linear regression and SWOT analysis. The results of this research conclude that: (1) the determinants of the regional financial capacity of Jambi Province where the variables of economic growth, investment and balancing funds do not have a significant and negative effect on regional financial capacity. Meanwhile, the remaining economic growth has a significant effect on decreasing regional financial capacity and regional original income and population have a significant positive effect on increasing regional financial capacity in Jambi Province; and (2) the strategy to improve the financial capacity of the region where Jambi Province is located is a diversification strategy that focuses on exploiting the long-term opportunities that Jambi Province has.